Efikasi Diri Merupakan Faktor Yang Berhubungan Dengan Resiliensi Keluarga Yang Memiliki Remaja Dengan Gangguan Jiwa Berat - Barimbing, Maryati Agustina (NHM PRESS, 2023)
Severe mental disorders in adolescents have an negative impact on sufferers and their families. This negative impact can be prevented and overcome when families have resilience, that is the ability to survive and fight the stressors. Factor related to family resilience based on the theory of